Faktor-Faktor Yang Mempengaruhi Kinerja Sistem Informasi Akuntansi(Studi Pada Pt Angkasa Pura I Bandara Adi Sumarmo) - Insani, Aulia; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2017)
The purpose of this research to examine and analyze the influence of the involvement of users, the ability of users, training and education of users, and top management support on the performance of accounting information systems at Angkasa Pura I Adi Sumarmo Airport. The amount of the sample in this research is 36 employees. The sampling techniques in this research uses saturated sample method, the entire population is used as a sample. The data analysis in this research uses the help of SPSS version 22. The analysis method that is used is multiple linear regression to test and prove the research hypothesis. The analysis showed that the involvement of users, the ability of users, training and education of users, and top management support have a significant effect on the performance of accounting information systems. This can be seen from the value t_count>t_tabel and the probability of < 0,05.